Current Methodological Pitfalls and Caveats in the Assessment of Exercise-Induced Changes in Peripheral Brain-Derived Neurotrophic Factor: How Result Reproducibility Can Be Improved - Nicolini, Chiara; Nelson, Aimee J. (Frontiers in Neuroergonomics, 2021)
Neural mechanisms, such as enhanced neuroplasticity within the motor system, underpin exercise-induced motor improvements. Being a key mediator of motor plasticity, brain-derived neurotrophic factor (BDNF) is likely to play an important role in mediating exercise positive effects on motor function. Difficulties in assessing brain BDNF levels in humans have drawn attention to quantification of blood BDNF and raise the question of whether peripheral BDNF contributes to exercise-related motor improvements. Methodological and non-methodological factors influence measurements of blood BDNF introducing a substantial variability that complicates result interpretation and leads to inconsistencies among studies. Here, we discuss methodology-related issues and approaches emerging from current findings to reduce variability and increase result reproducibility.